Penerapan Metode Qowaid dan Tarjamah terhadap Keterampilan Membaca bagi Siswa Kelas IV MI Hidayatul Ulum Benjeng Gresik - Husnul Fuadatun Nisa'; Hani'atul Khoiroh; Dzakiyatul Fuaidah (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2023)
This research was motivated by deficiencies in reading skills, namely difficulties in understanding Arabic texts due to a lack of insight into Arabic grammar and vocabulary at the Hidayatul Ulum Benjeng Gresik Elementary School. The Grammar and Translation Method is one of the methods of teaching Arabic for reading skills, and can help students understand Arabic texts easily by knowing the rules of translation. The formulation of the research problem is whether there is an influence of the application of the Grammar and Translation method on the fourth grade students of SD Hidayatul Ulum Benjeng Gresik and to what extent this influence exists. The purpose of this research is to determine the influence of the application of the Grammar and Translation method and the extent to which the influence of the application of this method is on the fourth grade students of SD Hidayatul Ulum Benjeng Gresik. This researcher used a quantitative approach with a pre-experimental design type. obtaining data through observation, tests and documentation. The results of this research show that there is an influence of the application of grammar and translation methods on fourth grade students at Hidayatul Ulum Elementary School Benjeng Gresik, with a post-test result of 1085 which is greater than the pre-test result of 845. There is a difference between the two tests which the test means 23.25 with a total of 12 students. The T-Table value is 1% of 3.11, and 5% of 2.20, thus the T-Count value is greater than the t table value, so the positive research hypothesis can be accepted.